MENCARI WARISAN NABI DI INDONESIA DALAM PERSPEKTIF SEJARAH - Djazimah, Nurul (Jurnal Studia Insania, 2015)
Indonesia is a country with the world?s third largest population; about 90 percent of the population is Muslims. The history of the Islam in this country can be traced back to descendants of the prophet Muhammad. They played an important role in disseminating Islamic teachings in the archipelago. Until now descandants of the prophet still engage in Islamic preaching activities, understanding the legacy of the prophet from historical perspective is instructive, for that will help clarify the making of Muslim civilition in the archipelago. The prophet sent his companions to the area now known as Indonesia. His predecesors continued this tradition of sending companions in preaching missions nost notably in the time Utsman ibn Affan. The Islamic spiritual link with Indonesia was concrete: one preserved clothing of the prophet and a flag used in one of this own battles were given to the Sultan of Banten as gifts. Indeed, the community of Islamic believers shares the legacy of the prophet regardless of their orgins. Most prominently among them have been the Islamic preachers and Muslim warriors.